Preparation method of carbon nanofiber

By preparing porous carbon nanofibers with array-shaped parallel pore structures, the problems of cyclic stability and capacity attenuation of potassium ion battery anode material are solved, and efficient potassium ion insertion and long life of the material are achieved.

CN119392410APending Publication Date: 2025-02-07ANHUI SCI & TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411579580.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The cyclic stability of potassium ion battery (KIBs) anode materials have poor capacity attenuation and severe capacity. The existing carbon-based anode materials have problems such as high preparation cost, low initial Coulomb efficiency, low reversible capacity and low cycle stability.

Method used

Cobalt acetate, polymethyl methacrylate (PMMA), polypropylene (PAN) and polystyrene (PS) are dissolved in N,N-dimethylformamide (DMF) to form a spinning liquid, and electrospinning is performed. The nanofibers were obtained and two high-temperature carbonization treatment was carried out to form porous carbon nanofibers with an array-shaped parallel pore structure.

Benefits of technology

As the anode material of potassium ion battery, this material has excellent capacity and cycle stability, can maintain a high reversible capacity under high current density, and maintain high battery performance after a long period of time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392410A_ABST
    Figure CN119392410A_ABST
Patent Text Reader

Abstract

A preparation method of carbon nanofibers is characterized in that cobalt acetate, polymethyl methacrylate (PMMA), polyacrylonitrile (PAN) and polystyrene (PS) are dissolved in N, N-dimethylformamide (DMF) to form a spinning solution, electrostatic spinning is carried out to obtain nanofibers, then two-stage high-temperature carbonization is carried out, the two-stage high-temperature carbonization temperature is 250-260 DEG C and 850-900 DEG C in sequence, the spinning solution is obtained by heating DMF to 50-60 DEG C, and the spinning solution is obtained by heating DMF to 50-60 DEG C and carrying out electrostatic spinning. Then adding cobalt acetate, PMMA, PAN and PS while stirring at 500-600 rpm, and continuously stirring for 10-12 hours to obtain the composite material. The nanofiber prepared by the method has an array-shaped parallel arrangement pore channel structure, is beneficial to the immersion of electrolyte, has excellent ionic conductivity and ultra-long battery life when being used as a positive electrode material of a potassium ion battery, has the capacity of 309 mA g <-1 > when the current density is 0.2 A g <-1 >, has the reversible capacity of 285 mA h g <-1 > after circulation for 100 times, and has the reversible capacity of 252 mA h g <-1 > after circulation for 3000 times.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of patent application number 202310059994.3, and the invention name is “A porous carbon nanofiber material with parallel pore structure and preparation method thereof”. Technical Field

[0002] The invention relates to the technical field of carbon fiber material preparation, and in particular to a method for preparing carbon nanofibers. Background Art

[0003] Potassium-ion batteries (KIBs) have become a promising alternative to lithium-ion batteries, but due to the + The ionic radius of Li (1.38 nm) is larger than that of Li + (0.76 nm), K + The intercalation / deintercalation process leads to volume expansion of the anode, which results in poor cycling stability of the anode material. Therefore, it remains a great challenge to develop suitable anode materials with high reversibility and stable structure for KIBs.

[0004] According to existing reports, K ions can be inserted into the graphite interlayer of carbon nanomaterials to form KC8 phase (theoretical capacity is 278 mAh g -1 ). However, due to the large ionic radius of K ions, the (002) plane distance of the graphite layer expands from 0.335nm to 0.532nm during the intercalation process, resulting in a large volume change of the anode material (about 61%), making the carbon nanomaterials have poor cycle stability and severe capacity decay. In order to buffer and overcome the huge volume expansion of the anode material, various carbon nanostructures such as soft carbon, hard carbon, graphene, carbon nanotubes (CNT), carbon fiber, carbon foam and amorphous carbon have been developed as KIB anodes in the prior art. However, these carbon-based anode materials still have various disadvantages, including high preparation cost, low initial coulombic efficiency (ICE), low reversible capacity and low cycle stability. Therefore, the controllable synthesis of ordered porous carbon anode materials remains a huge challenge. Summary of the invention

[0005] The present invention aims to provide a method for preparing a porous carbon nanofiber material having an array-shaped pore structure. The carbon nanofiber prepared by the method has excellent capacity and cycle stability when used as a positive electrode material for potassium ion batteries (KIBs).

[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing carbon nanofibers, characterized in that cobalt acetate, polymethyl methacrylate (PMMA), polyacrylonitrile (PAN) and polystyrene (PS) are dissolved in N,N-dimethylformamide (DMF) to form a spinning solution, nanofibers are obtained by electrospinning, and then two-stage high-temperature carbonization, the two-stage high-temperature carbonization temperatures are 250-260°C and 850-900°C respectively, the spinning solution is obtained by heating DMF to 50-60°C, then adding cobalt acetate, PMMA, PAN and PS under stirring at 500-600rpm, and continuously stirring for 10-12h.

[0007] In the present invention, cobalt acetate is used as a catalyst, PMMA, PAN and PS are used as composite carbon sources, and the composite of different multi-path carbon sources forms a fiber structure with a smaller diameter under the action of the catalyst cobalt acetate and the participation of PMMA. PAN and PS form preliminary pores in the fiber, and after two stages of high-temperature carbonization and decomposition, parallel pores arranged in an array are formed, and pores with a larger diameter are formed in the fiber with a smaller diameter. When the porous carbon nanofiber with this structure is used as an anode material for potassium ion batteries, K + The embedding and de-embedding of the material can be effectively suppressed.

[0008] Furthermore, the mass volume ratio of the cobalt acetate, PMMA, PAN, PS and DMF is 0.6-0.7 mg: 0.5 mg: 0.9 g: 0.3 mg: 10 mL.

[0009] Furthermore, the electrospinning described above has a spinning needle and a collector of 17-20 cm, a feed rate of 1 mL / h, and a spinning voltage of 18 kV.

[0010] Furthermore, after the spinning was completed, the collected fibers were dried at 60°C.

[0011] Furthermore, the carbonization at both ends is specifically carried out by heating the temperature to 250-260°C at 2°C / min in an air atmosphere, keeping the temperature for 2 hours, then heating the temperature to 850-900°C at 5°C / min, introducing a mixed gas of H2 and Ar, and keeping the temperature for 2 hours.

[0012] Furthermore, the volume ratio of H2 to Ar in the mixed gas is 5:95.

[0013] Furthermore, the method for preparing the carbon nanofibers is characterized by comprising the following steps: Step 1: Electrospinning to prepare fibers (1) Heat DMF to 50-60°C, then add cobalt acetate, PMMA, PAN and PS under stirring at 500-600 rpm, and continue stirring for 10-12 hours to form a spinning solution. The mass volume ratio of cobalt acetate, PMMA, PAN, PS and DMF is 0.6-0.7 mg: 0.5 mg: 0.9 g: 0.3 mg: 10 mL; (2) electrospinning the spinning solution, wherein the distance between the spinning needle and the collector is 17-20 cm, the feed rate is 1 mL / h, the spinning voltage is 18 kV, and after the spinning is completed, the collected fibers are dried at 60° C.; Step 2: High temperature carbonization treatment The dried fiber was heated to 250-260°C at 2°C / min in an air atmosphere, kept warm for 2 hours, then heated to 850-900°C at 5°C / min, and then a mixed gas of H2 and Ar was introduced and kept warm for 2 hours, with a volume ratio of H2 to Ar being 5:95.

[0014] The carbon nanofibers prepared by the above method are porous carbon nanofibers with a parallel pore structure. The fiber diameter is 50 nm and has an array-arranged through-hole structure parallel to the fiber.

[0015] The present invention has the following technical effects: The porous carbon nanofiber material with an array of parallel pores prepared by the method of the present invention has a diameter of about 50 nanometers and a length of several tens of micrometers. The parallel pores in its structure are conducive to the infiltration of electrolytes. Therefore, when it is used as a positive electrode material for potassium ion batteries, it has excellent ion conductivity and ultra-long battery life. When the porous carbon nanofiber material with an array of parallel pores is used as a positive electrode material for potassium ion batteries, the current density is 0.2A g -1 When the capacity is 309mA g -1 After 100 cycles, the reversible capacity is 285 mA hg -1 After 3000 cycles, it has a current of 252 mA hg -1 Reversible capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 : Schematic diagram of the structure of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention.

[0017] Figure 2 : Scanning electron microscope image of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention.

[0018] Figure 3 : Transmission electron micrograph of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention.

[0019] Figure 4 : X-ray diffraction pattern of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention.

[0020] Figure 5 : Rate-cycle performance comparison curve of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention and the solid carbon nanofiber prepared in Comparative Example 1 at different current densities.

[0021] Figure 6 : Comparison of the cyclic stability of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention and the solid carbon nanofiber prepared by comparison 1.

[0022] Figure 7 : Rate-cycle performance comparison curve of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention and the solid carbon nanofiber prepared in Comparative Example 2 at different current densities.

[0023] Figure 8 : Comparison of the cyclic stability of the porous carbon nanofiber material with array-like parallel pore structure prepared by the present invention and the solid carbon nanofiber prepared by comparison 2. DETAILED DESCRIPTION

[0024] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0025] Example 1 A method for preparing a carbon nanofiber material is characterized by following the steps: Step 1: Electrospinning to prepare fibers (1) DMF was heated to 50°C, and then cobalt acetate, PMMA, PAN and PS were added under stirring at 600 rpm and continued to stir for 12 h to form a spinning solution. The mass volume ratio of cobalt acetate, PMMA, PAN, PS and DMF was 0.7 mg: 0.5 mg: 0.9 g: 0.3 mg: 10 mL; (2) electrospinning the spinning solution, wherein the length of the spinning needle and the collector is 17 cm, the feed rate is 1 mL / h, the spinning voltage is 18 kV, and after the spinning is completed, the collected fibers are dried at 60 ° C; Step 2: High temperature carbonization treatment The dried fiber was heated to 260°C at 2°C / min in an air atmosphere and kept warm for 2 hours. Then, the temperature was raised to 900°C at 5°C / min, and a mixed gas of H2 and Ar was introduced and kept warm for 2 hours. The volume ratio of H2 and Ar was 5:95.

[0026] Figure 1 Schematic diagram of the structure of the porous carbon nanofiber with array-arranged parallel pore structure prepared by the present invention, such as Figure 2 and Figure 3 As shown, the average diameter of the carbon nanofibers prepared by the present invention is 50 nm, and the fibers have channels parallel to the fibers to form an array arrangement, and the channel diameter is large, which is beneficial to K + Effectively relieve K + The volume deformation caused by the embedding and unembedding process. The X-ray diffraction pattern of the carbon nanofiber prepared by the present invention is as follows Figure 4 As shown, the present invention forms a pure carbon material without any residue of carbon raw material and cobalt acetate as a catalyst.

[0027] Comparative Example 1: Compared with Example 1, PMMA was not added when preparing the spinning solution, and the remaining steps were consistent with Example 1.

[0028] Although the carbon nanofibers prepared in Comparative Example 1 also formed a parallel pore structure, the diameter of the carbon nanofibers was larger, with an average diameter of 500 nm, and the pore size was smaller than that in Example 1, which was not conducive to K + A large number of embedding, K + The embedding and unembedding process can easily cause a large volume change in the carbon nanofiber material. Figure 5 and Figure 6 As shown in the figure, when the carbon nanofibers prepared in Comparative Example 1 and Example 1 are used as positive electrode materials for potassium ion batteries, the current density is 0.2 A g -1 309 mAh g -1 After 100 cycles, its reversible capacity is 285 mA h g -1 After 3000 cycles, it has a capacitance of 252 mA hg -1 The reversible capacity of carbon nanofibers prepared in Comparative Example 1 was 0.2 A g -1 When the -1 After 3000 cycles, the capacity decayed severely and was only 22 mA h g -1 Reversible capacity.

[0029] Comparative Example 2 Compared with Example 1, the difference is that PAN and PS are not added when preparing the spinning solution, and the other steps are consistent with Example 1. The prepared carbon nanofibers are solid structures without array-arranged parallel channels inside. Figure 7 and Figure 8 As shown, the carbon nanofibers prepared in Comparative Example 2 were -1 When the -1 After 100 cycles, the reversible capacity is 67 mA h g -1 .

[0030] Example 2 A method for preparing carbon nanofibers, characterized by following the steps: Step 1: Electrospinning to prepare fibers (1) DMF was heated to 55°C, and then cobalt acetate, PMMA, PAN and PS were added under stirring at 550 rpm and stirred for 11 h to form a spinning solution. The mass volume ratio of cobalt acetate, PMMA, PAN, PS and DMF was 0.65 mg: 0.5 mg: 0.9 g: 0.3 mg: 10 mL; (2) electrospinning the spinning solution, wherein the length of the spinning needle and the collector is 18 cm, the feed rate is 1 mL / h, the spinning voltage is 18 kV, and after the spinning is completed, the collected fibers are dried at 60 ° C; Step 2: High temperature carbonization treatment The dried fiber was heated to 255°C at 2°C / min in an air atmosphere and kept at this temperature for 2 hours. Then, the temperature was raised to 880°C at 5°C / min, and a mixed gas of H2 and Ar was introduced and kept at this temperature for 2 hours. The volume ratio of H2 to Ar was 5:95.

[0031] When the carbon nanofibers prepared in this example are used as the positive electrode material of potassium ion batteries, the current density is 0.2 A g -1 305 mA hg -1 After 3000 cycles, it has a capacity of 260 mA hg -1 Reversible capacity.

[0032] Example 3 A method for preparing carbon nanofibers, characterized by following the steps: Step 1: Electrospinning to prepare fibers (1) DMF was heated to 60°C, and then cobalt acetate, PMMA, PAN and PS were added under stirring at 500 rpm and continued to stir for 10 h to form a spinning solution. The mass volume ratio of cobalt acetate, PMMA, PAN, PS and DMF was 0.6 mg: 0.5 mg: 0.9 g: 0.3 mg: 10 mL; (2) electrospinning the spinning solution, wherein the length of the spinning needle and the collector is 20 cm, the feed rate is 1 mL / h, the spinning voltage is 18 kV, and after the spinning, the collected fibers are dried at 60 °C; Step 2: High temperature carbonization treatment The dried fiber was heated to 250°C at 2°C / min in an air atmosphere and kept warm for 2 hours. Then, the temperature was raised to 850°C at 5°C / min, and a mixed gas of H2 and Ar was introduced and kept warm for 2 hours. The volume ratio of H2 and Ar was 5:95.

[0033] When the carbon nanofibers prepared in this example are used as the positive electrode material of potassium ion batteries, the current density is 0.2 A g -1 316 mA hg -1 After 3000 cycles, it has a capacity of 251mA hg -1 Reversible capacity.

Claims

1. A method for preparing carbon nanofibers, characterized in that: Cobalt acetate, polymethyl methacrylate (PMMA), polyacrylonitrile (PAN) and polystyrene (PS) are dissolved in N,N-dimethylformamide (DMF) to form a spinning solution, and nanofibers are obtained by electrospinning, followed by two-stage high-temperature carbonization, the two-stage high-temperature carbonization temperatures are 250-260°C and 850-900°C respectively. The spinning solution is obtained by heating DMF to 50-60°C, then adding cobalt acetate, PMMA, PAN and PS under stirring at 500-600rpm, and continuing stirring for 10-12h.

2. The method for preparing carbon nanofibers according to claim 1, characterized in that: The mass volume ratio of the cobalt acetate, PMMA, PAN, PS and DMF is 0.6-0.7 mg: 0.5 mg: 0.9 g: 0.3 mg: 10 mL.

3. A method for preparing carbon nanofibers according to claim 1 or 2, characterized in that: The electrospinning method is as follows: the distance between the spinning needle and the collector is 17-20 cm, the feed rate is 1 mL / h, and the spinning voltage is 18 kV.

4. A method for preparing carbon nanofibers according to any one of claims 1 to 3, characterized in that: The carbonization at both ends is specifically carried out by heating to 250-260°C at 2°C / min in an air atmosphere, keeping the temperature for 2 hours, then heating to 850-900°C at 5°C / min, introducing a mixed gas of H2 and Ar, and keeping the temperature for 2 hours.

5. A method for preparing carbon nanofibers, characterized in that: The steps include: Step 1: Electrospinning to prepare fibers (1) Heat DMF to 50-60°C, then add cobalt acetate, PMMA, PAN and PS under stirring at 500-600 rpm, and continue stirring for 10-12 hours to form a spinning solution. The mass volume ratio of cobalt acetate, PMMA, PAN, PS and DMF is 0.6-0.7 mg: 0.5 mg: 0.9 g: 0.3 mg: 10 mL; (2) electrospinning the spinning solution, wherein the distance between the spinning needle and the collector is 17-20 cm, the feed rate is 1 mL / h, the spinning voltage is 18 kV, and after the spinning is completed, the collected fibers are dried at 60° C.; Step 2: High temperature carbonization treatment The dried fiber was heated to 250-260°C at 2°C / min in an air atmosphere, kept warm for 2 hours, then heated to 850-900°C at 5°C / min, and then a mixed gas of H2 and Ar was introduced and kept warm for 2 hours, with a volume ratio of H2 to Ar being 5:95.